Coherence of Rabi oscillations with spin exchange - C. Kiehl; D. Wagner; T.-W. Hsu; S. Knappe; C. A. Regal; T. Thiele (Physical Review Research, 2023)
Rabi measurements in atomic vapor cells are of current interest in a range of microwave imaging and sensing experiments, but are increasingly in a parameter space outside of theoretical studies of coherence defined by spin-exchange collisions. Here, we study the coherence of Rabi oscillations in vapor cells by employing continuous nondestructive readout of the hyperfine manifold of ^{87}Rb using Faraday rotation. We develop a full model for spin-exchange coherence for hyperfine transitions that takes into account a nonstatic population distribution. In this regime, Rabi oscillations exhibit nontrivial time-domain signals that allow verification of vapor-cell parameters. We find excellent agreement between theory and experiment, which will aid in benchmarking sensitivities of Rabi measurement applications.